Modulation of Mechanical Interactions by Local Piezoelectric Effects. (8th September 2016) - Brown, Cameron P.; Boyd, Jennifer L.; Palmer, Antony J.; Phillips, Mick; Couture, Charles‐Andre; Rivard, Maxime; Hulley, Philippa A.; Price, Andrew J.; Ruediger, Andreas; Légaré, Francois; Carr, Andrew J.
Abstract : Piezoelectricity is a well‐established property of biological materials, yet its functional role has remained unclear. Here, a mechanical effect of piezoelectric domains resulting from collagen fibril organisation is demonstrated, and its role in tissue function and application to material design is described. Using a combination of scanning probe and nonlinear optical microscopy, a hierarchical structuring of piezoelectric domains in collagen‐rich tissues is observed, and their mechanical effects are explored in silico. Local electrostatic attraction and repulsion due to shear piezoelectricity in these domains modulate fibril interactions from the tens of nanometre (single fibril interactions) to the tens of micron (fibre interactions) level, analogous to modulated friction effects. The manipulation of domain size and organisation thus provides a capacity to tune energy storage, dissipation, stiffness, and damage resistance. Abstract : Domains of piezoelectricity passively modulate interactions in mechanical systems. Mechanical analysis of piezoelectricity and its manifestation in collagen fibril interactions reveal that electrostatic attraction within domains and repulsion at domain boundaries mediate mesoscale mechanical properties. This mechanism can be applied to functionalize synthetic systems by the introduction of passive piezoelectric materials to tune mechanical performance, damage resistance, or tribology.